The systemic-praxeological approach to the methodology of primary scientific activity of the management science system - Witczak, Hubert (Research Papers in Economics and Finance, 2020)
The scientific methodology of management science (MSc) is consistent in terms of direction with the overall methodology of sciences. Still, it continues to pose significant challenges. One such challenge is the problem of system characteristics of MSc methodology at the highest level of scientific practice, i.e. praxeology and systems theory. There are also the problems of MSc synthesis, i.e. the definition of its universal scope, in the light of its increasing diversity and specialisation of domains. This paper aims to elaborate on the achievements to date in management science on the grounds of the systemic-praxeological approach, scientific synthesis of methodology, with a particular focus on the role of reasoning and inference. My assertion is that methodology is a subsystem of the core of primary scientific activity of MSc, comprising the com- ponents of scientific practice focused around the scientific method (methods). Its objective domain extends beyond the cognitive function, also encompassing value assignment, determination of post-diagnosis scientific action, decisions about scientific models and implementation of scientific models –CARNI system. The scientific methodology of MSc is specifically a product of scientific problems as well as the goals, principles and methods used to solve them, forming an exceedingly complex system.